Comparative effects of exercise type and dose on depression in children and adolescents: a network meta-analysis - Cao, Xiaofeng (Frontiers in Psychology, 2025)
BackgroundThis study seeks to evaluate the comparative effectiveness of various physical activity modalities: including aerobic (AT), resistance (RT), flexibility (FT), and combined aerobic-resistance (AT + RT) training, in reducing depressive symptoms among children and adolescents, with the aim of determining the most effective type and dosage for optimizing mental health outcomes in this population.MethodsFollowing a comprehensive search of PubMed, MEDLINE, Embase, PsycINFO, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, and other databases, studies were selected according to stringent inclusion and exclusion criteria. Quality assessment, data extraction, and subsequent analysis were conducted using RevMan 5.3 and Stata 16.0 software.ResultsSeventeen high-quality studies, involving 1,357 young participants, were included in this meta-analysis to explore the impacts of the four exercise types on depressive symptoms. Network Meta-Analysis results indicated that RT (SMD = −0.52, 95% CI: −0.95 to −0.09) were significantly more effective than AT (SMD = −0.40, 95% CI: −0.56 to −0.25) and AT + RT (SMD = −0.30, 95% CI: −0.49 to −0.10) in reducing depressive symptoms (p < 0.05). We found that exercising for 20 ~ 30 min per session (SMD = −0.35, 95% CI: −0.59 to −0.11), three times a week (SMD = −0.42, 95% CI: −0.67 to −0.16), over a 6 ~ 8 week period (SMD = −0.74, 95% CI: −0.95 to −0.52) yielded the most significant reductions in depressive symptoms (p < 0.01).ConclusionDifferent exercise types, including AT, RT, and AT + RT, can effectively reduce depressive symptoms in children and adolescents, with RT emerging as the most effective approach. It is recommended that children and adolescents participate in physical activity at least three times weekly for 6 ~ 8 weeks, with each session lasting 20 ~ 30 min. Greater frequency and duration may lead to even more substantial improvements in depressive symptoms.